EDUCATION ON DENGUE FEVER CONTROL AND ENVIRONMENTAL HEALTH HYGIENE - Diannita, Catharina Guinda; Sihombing, Riama Marlyn; Patrisia, Ineke; Sampepadang, Mega; Siregar, Deborah; Cucunawangsih, Cucunawangsih (Universitas Airlangga, 2024)
Introduction: Dengue is a disease of global public health concern because mosquito-borne viruses can spread rapidly, especially in tropical and sub-tropical regions such as Indonesia. The purpose of community service activities is to increase public knowledge about dengue control and recognize environmental health hygiene behavior. Methods: The learning method used is a medical examination and health education. The target participants are 100, however, the participants who fully participated in the activity were around 60. Results: After carrying out educational activities, the results of increasing participants' knowledge about dengue control and environmental health hygiene were found. The evaluation has only been carried out in the cognitive domain, while the psychomotor realm has not been carried out because this activity is only carried out once, it is necessary to have continuous activities so that there is an increase in cognitive, affective and psychomotor abilities regarding health problems in the community. Conclusion: Participants' knowledge related to dengue fever control and environmental health hygiene was found to slightly increase.